Annual editions / entrepreneurship. - Price, Robert W. (Annual editions., 2006)
Students are motivated to study entrepreneurship for a variety of reasons. This text is aimed at preparing them to initiate their own venture, work in an emerging venture, or be employed in a company that provides goods and services to emerging firms ... This text will provide you with a view of the entrepreneurial process from idea to exit.-Pref.